PENGARUH METODE BERNYANYI TERHADAP PENGUASAAN KOSAKATA PADA ANAK USIA DINI - Agis Nurfadilah (CV. ADIBA ASIHA AMIRA, 2025)
This research was motivated by an observation that identified problems in vocabulary mastery among early childhood children. Many students still lacked vocabulary mastery. This study aimed to determine the effect of singing on vocabulary mastery in early childhood children. The purpose of this study was to determine the differences in vocabulary mastery among early childhood children in Group B of RA Al-Patwa Cicukang, Bandung Regency, in the experimental and control classes. Vocabulary is one aspect related to children's language development. Children's vocabulary skills can be demonstrated by their ability to play with words and understand their meanings. One method that can be used is singing. By presenting it in an interesting and enjoyable way during the learning process, it can stimulate children to understand things quickly and help them learn vocabulary with a sense of enjoyment. The author employed a quantitative research method, employing a quasi-experimental method. This study also used quasi-research data to determine the effect of variable X (singing method) on variable Y (vocabulary mastery). The subjects were children in Group B of RA Al-Patwa Cicukang, Bandung Regency. Data collection techniques used were observation and documentation. The data were then analyzed using validity, reliability, normality, and hypothesis testing. The results showed that the highest pretest score was 50 and the lowest score was 29.16. The pretest average was 38.885, rounded to 39, which falls into the